An analysis of the effectiveness of a state trauma system: Treatment at designated trauma centers is associated with an increased probability of survival. Issue 4 (April 2015) - Ashley, Dennis W.; Pracht, Etienne E.; Medeiros, Regina S.; Atkins, Elizabeth V.; NeSmith, Elizabeth G.; Johns, Tracy J.; Nicholas, Jeffrey M.
Abstract : BACKGROUND: States struggle to continue support for recruitment, funding and development of designated trauma centers (DTCs). The purpose of this study was to evaluate the probability of survival for injured patients treated at DTCs versus nontrauma centers. METHODS: We reviewed 188, 348 patients from the state's hospital discharge database and identified 13, 953 severely injured patients admitted to either a DTC or a nontrauma center between 2008 and 2012. DRG International Classification of Diseases—9th Rev. Injury Severity Scores (ICISS), an accepted indicator of injury severity, was assigned to each patient. Severe injury was defined as an ICISS less than 0.85 (indicating ≥15% probability of mortality). Three subgroups of the severely injured patients were defined as most critical, intermediate critical, and least critical. A full information maximum likelihood bivariate probit model was used to determine the differences in the probability of survival for matched cohorts. RESULTS: After controlling for injury severity, injury type, patient demographics, the presence of comorbidities, as well as insurance type and status, severely injured patients treated at a DTC have a 10% increased probability of survival. The largest improvement was seen in the intermediate subgroup. CONCLUSION: Treatment of severely injured patients at a DTC is associated with an improved probability of survival. This argues for continued resources in support of DTCs within a defined statewide network. LEVEL OF EVIDENCE: Epidemiologic study, level III.